Nowe systemy usuwania związków azotu ze ścieków = New systems of nitrogen compounds disposal from sewages - Mazurkiewicz, Marta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article contains the latest literature data concerning new possibilities of removing nitrogen compounds from sewage. New systems known as: ANAMMOX, CANON, SHARON, OLAND, BABE weve introduced as alternative methods to traditionally run processes of nitrification and denitrification in biological sewage treatment. These systems are featured by higher efficiency and low oxygen demand.
Keywords: nitryfikacja; denitryfikacja; systemy usuwania azotu ze ścieków; nitrification; denitryfication; the systems of nitrogen remowal from sewage